COURSE ON LINGUISTIC EXPLANATION LINKED TO METHODOLOGICAL STEREOTYPES IN SCIENTIFIC WRITING BY UNIVERSITY PROFESSIONALS - Cruz-Camacho, Lisvette (2022)
There is acceptance and establishment of methodological stereotypes by professionals at the University of Medical Sciences of Villa Clara, Cuba. This is due to theoretical ignorance about the interrelation of linguistics with the methodology of research in the conscious expression of scientifi c language. Th e situation has served as a motivation to these authors to reverse it through the design and development of a course aimed at these university students. The essence of the course lies in the linguistic explanation –applied linguistics–, linked to methodological stereotypes in scientifi c writing. However, in parallel with the teaching process, a study was conducted to perceive possible conceptual changes in students. Hence, the objective of: is research is to expose the experience and educational-research results inherent to the referred course. Methodologically, the heuristic proceedings of language teaching, as well as the literary analysis in the study of the language fi gured in diff erent styles were used for teaching. In the investigative process, the theoretical methods- synthesis and induction-deduction were used to obtain, process, and analyze the information. Empirical methods of observation and documentary review were also used, in order to obtain the primary data of the diagnosis, as well as the final data derived from the evaluation and of a survey applied when completing the course. The mathematical method of percentage analysis served to tabulate and process the information obtained. As for the results, a conceptual change in students may be found from the diagnosis; phase where these did not notice the relationship between methodological patterns and linguistic science. By completing the course, the students proved to be aware of that interrelation. Finally, the authors consider that the greatest significance of the course lies in the reflection, discussion, and analysis of facts sometimes unnoticed by the professionals of science; evidently, a marked purpose is to move static and dogmatic thought through reasons argued and shared, in this case, by the generality of the group.